Chinese Self, Australian Other: Chinese as a Foreign Language Teacher Identity Construction in Australian Contexts - Han, Yu; Ji, Xiaoyan (Frontiers in Psychology, 2021)
Research in the Chinese as a foreign language (CFL) education field has been increasing in the past decade; however, studies on CFL teacher identity have been limited in number. To bridge the gap, this study employed a qualitative method to explore Chinese CFL teachers’ identity formation and reformation in Australian contexts. A Chinese-Australian CFL teacher training program was enrolled in the study to examine the challenges, struggles, and developments of Chinese background CFL teachers who moved to Australian contexts to pursue professional growth. Five master’s theses and three interview participants were included to paint a picture of how Chinese CFL teachers interact internally and externally with the new environment. With the help of Mead’s theory of self and other, we found that Chinese CFL teachers’ identity formation and reformation in Australian classrooms is deeply influenced by their self identification and their integration with other in the community. Cultural connectedness is a key for organizational attitudes in the relationship of self and other. Chinese CFL teachers were found lacking the wholeness of self in Australian contexts, which led to obstacles in teacher identity construction. Insufficient communication between self and other resulted in their positioning crisis.